PENGARUH SERVICESCAPES TERHADAP RESPON PELANGGAN DAN RESPON PRAMUSAJI PADA FOOD AND BEVERAGE DEPARTMENT (STUDI KASUS DI CAFE DE DAPUR SANUR) - I Wayan Pantiyasa (Institut Pariwisata dan Bisnis Internasional, 2017)
This research aimed to investigate the effects of servicescapes to the responses of the customers and waiters at food and beverage service in Café de Dapoer, The Oasis Lagoon Sanur. The change in physical environment including renovation, rejuvenation, as well as the changing design and concept of Café de Dapoer, attracted the researchers to conduct deeper analysis. Independent variable of analysis was the servicescapes (X), while the dependent variables were the response of the waiters (Y1), and the response of the customers (Y2) at Café de Dapoer, The Oasis Lagoon Sanur. The respondents of this research were 20 waiters and 40 customers at Café de Dapoer, The Oasis Lagoon Sanur. The method of census was used to collect samples from the waiters, while jugmental sampling was used to collect samples from the customers, with certain conditions. The technique of data collection used questionnaires with semantic differential scale. The research instruments were tested using validity test, reliability test, and normality test. Hypothesis testing applied the partial t test and the average comparison analysis. From the result of simple regression analysis, it could be concluded that the entire variables of servicescapes had positive and significant effects, both to the response of the waiters (97.1% were effected by servicescapes variables and 2.9% were effected by other variables) and to the reponse of the customers (64.3% were effected by servicescapes variables and 35.7% were effected by other variables). From the result of mean comparison, the response of the waiters was positively higher, that was 0.1799, compared to the response of the customer. The findings showed there were some factors with the values under the average standard, such as the temperature, air quality, lightning, function, signage, style of décor, fear, physical fit, afflication, and staylonger, which were later used as the base of evaluation.